Modelo de Gestión Administrativa para la Comercializadora Otavalito en la Parroquia Miguel Egas. - Otavalo Lema, Saúl (2015)
This study came about the importance to the quality of administrative and finan Project management for small business “Otavalito”. The theoretical structural framework was based on the bibliographical resources and the technical observation to oversee the subject study of this problem. Once the situational analysis was done, it was confirmed an inadequate administrative financial management system in several areas. This “Otavalito” small business doesn´t have any administrative tools when the personnel were interviewed; and this is the result why they generated low sales. In this Project, I propose to improve and solve the problems and I will also give some recommendations to contribute to diminish this weakness within the administrative and financial project management at this small business “Otavalito”.